Hemoglobin vancouver [α2β2 73(E17) Asp→ Tyr]: Its structure and function - R. T. Jones (2018)
Hemoglobin Vancouver is a new abnormal hemoglobin with an amino acid substitution of the normal aspartyl residue 73 of the β chain by a tyrosyl residue. It was discovered in a man of Chinese descent in association with β thalassemia. It was subsequently detected in a sister in association with normal Hb A. The oxygen affinity of the abnormal hemoglobin is decreased but its subunit interaction is normal. The Bohr effect may be slightly increased. This is the fourth abnormal hemoglobin to be found with a substitution at β73. The others are Hb C-Harlem (α < inf > 2 < /inf > β < inf > 2 < /inf > 6Glu→Val and 73 Asp→Asn), Hb Korle-Bu (α < inf > 2 < /inf > β < inf > 2 < /inf > 73 Asp→Asn), and Hb Mobile (α < inf > 2 < /inf > β < inf > 2 < /inf > 73 Asp→Val). Although Hb Mobile was found in the present studies to have a decreased affinity for oxygen, Hbs C-Harlem and Korle-Bu have been reported to be normal. These observations of functional differences for variants of β73 added to earlier observations of the role of the normal β73 residue to the aggregation of sickle deoxyhemoglobin indicate that this position of the molecule may be important in intra as well as intermolecular interactions. © 1976 Springer-Verlag.